2010
DOI: 10.1128/aem.00930-09
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in Cronobacter sakazakii Biofilm Formation

Abstract: Cronobacter spp. are opportunistic food-borne pathogens that can cause severe and sometimes lethal infections in neonates. In some outbreaks, the sources of infection were traced to contaminated powdered infant formula (PIF) or contaminated utensils used for PIF reconstitution. In this study, we investigated biofilm formation in Cronobacter sakazakii strain ES5. To investigate the genetic basis of biofilm formation in Cronobacter on abiotic surfaces, we screened a library of random transposon mutants of strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…[88][89][90] Two hypothetical proteins have been newly described as possible adhesins engaged in biofilm formation in Cronobacter (ESA_00281 and ESA_00282). 91 Iverson et al 92 reported that Cronobacter was able to adhere to silicon, stainless steel, polycarbonate and latex with apparently greater attachment occurring with EPS producing bacteria. Colanic acid (CA) was identified as an EPS component in Cronobacter spp.…”
Section: Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[88][89][90] Two hypothetical proteins have been newly described as possible adhesins engaged in biofilm formation in Cronobacter (ESA_00281 and ESA_00282). 91 Iverson et al 92 reported that Cronobacter was able to adhere to silicon, stainless steel, polycarbonate and latex with apparently greater attachment occurring with EPS producing bacteria. Colanic acid (CA) was identified as an EPS component in Cronobacter spp.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…The invasion studies with human intestinal (INT407) cells showed the contribution of Outer membrane protease cpa Provides resistance against bactericidal activity of serum; activates plasminogen and inactivates a2-AP 65,66 Sialic acid utilization nanAKT Confers in pathogenesis 71 Iron acquisition system iuc Encodes an iron-uptake system mediated by the active siderophorethat plays a role in iron transport and regulation 67,73 Efflux system ibeB Encodes copper and silver resistance cation efflux system facilitating invasion of brain microvascular endothelial cells (BMEC) 23 Proteolytic enzymes zpx Cause cell deformation and rounding of cells 83 Lipopoysaccarides Chromosomal encoded genes Disrupt epithelial tight junctions 91,102 Type III hemolysin hly Hemolytic activity 66,90 both microfilaments and microtubules from host and bacterial ompA. [69][70][71] Mittal and co-workers 72 reported that OmpA-positive isolates breach blood-brain barrier and invade central nervous system (CNS) causing clinical manifestations.…”
Section: Outer Membrane Proteins (Omps)mentioning
confidence: 99%
“…Biofilm formation is of special importance in the food industry, because biofilms can act as a source of microbial contamination that might lead to spoilage of foods or contamination of food products undergoing processing (Lehner et al, 2005;Hartmann et al, 2010). Biofilms of Cronobacter formed on feeding areas and on equipment surfaces used in formula preparation are thought to have contributed to several neonatal outbreaks .…”
Section: Biofilm Formationmentioning
confidence: 99%
“…38 Environmental reservoirs C. sakazakii is a ubiquitous bacterium found in a wide variety of reservoirs in the environment; from flies 39 to plants such as wheat, rice, herbs and spices 40 or meat and other common household foods. 41 The wide variety of environments in which C. sakazakii is present, indicates that it has developed various traits that increase survival in difficult conditions, e.g., resistance to UV irradiation, 42 the ability to adhere to various surfaces due to fimbriae formation, 42 biofilm formation 43 and the ability to survive desiccation. 7,9,44 The ability of C. sakazakii to survive in low water environments is a unique stress survival strategy which is linked with survival and persistence of the pathogen in powdered infant formula (PIF), subject to an a w of »0.2 (inhospitable to most micro-organisms).…”
Section: Antibiotic Resistance and Alternative Means Of Controlmentioning
confidence: 99%
“…Furthermore, this study outlined 3 basic adhesion patterns for C. sakazakii: diffuse adhesion, formation of localized clusters and a mixed phenotype. 71 While the ability of C. sakazakii to adhere to the tested cell models was independent of bacterial fimbrae formation, 71 Hartmann et al investigated the adherence efficiency of selected mutants of C. sakazakii strain ES5 to Caco-2 cells and found that the absence of flagella reduced the adherence ability of the bacterium, 43 demonstrating that flagella are important for this process. Others investigated adherence of clinical isolates from an outbreak in France.…”
mentioning
confidence: 99%